Determinasi Tingkat Keparahan Stunting Pada Balita: Peran Riwayat ASI Eksklusif dan Status Sosial Ekonomi - Linda Yanti; Untari Fajar Suryani; Intan Dyah Rahmawati (SEHATI: Jurnal Kesehatan, 2026)
Stunting is a chronic nutritional problem that reflects impaired linear growth resulting from the interaction of biological, social, and environmental factors since early life. The prevalence of stunting remains high, as indicated by national data showing rates of 24.4% in 2021 and 21.6% in 2022. This study aimed to analyze the determinants of stunting severity among children under five based on a history of exclusive breastfeeding and household socioeconomic status. This study employed an observational analytic design with a cross-sectional approach using secondary data obtained from medical records of children under five at Sokaraja I Primary Health Center, Banyumas Regency. The study sample consisted of 328 stunted children selected through total sampling. Stunting severity was classified into stunted and severely stunted based on height-for-age (HAZ) indicators according to WHO standards. Independent variables included a history of exclusive breastfeeding and household socioeconomic status. Data were analyzed using the Chi-square test with a significance level of p 0.05. The results showed a statistically significant association between a history of exclusive breastfeeding and stunting severity, in which children who did not receive exclusive breastfeeding were more likely to experience more severe stunting. In addition, household socioeconomic status was significantly associated with stunting severity, with a higher proportion of severe stunting observed among children from low-income families. In conclusion, stunting severity among children under five is associated with exclusive breastfeeding practices and household socioeconomic conditions, highlighting the need for comprehensive stunting prevention strategies through strengthened midwifery care and multisectoral approaches